2008
DOI: 10.1002/ijc.23606
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein and colorectal cancer risk: A systematic review of prospective studies

Abstract: C-reactive protein is a sensitive but nonspecific systemic marker of inflammation. Several prospective studies have investigated the association of prediagnostic circulating C-reactive protein concentrations with the development of colorectal cancer, but the results have been inconsistent. We performed a systematic review of prospective studies of the association between prediagnostic measurements of circulating high-sensitivity C-reactive protein and development of invasive colorectal cancer. Authors of origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 40 publications
9
131
1
2
Order By: Relevance
“…In accordance with the result of previous meta-analysis (Heikkila et al, 2009), less epidemiologic studies suggested a significant association between the elevated CRP levels and an increased risk of prostate and breast cancer (Platz et al, 2004;Trichopoulos et al, 2006), although a role for chronic inflammation in prostate (Haverkamp et al, 2008) and breast cancer (Ben-Baruch, 2003) has been identified. More controversy seemed to be from colorectal cancer (Otani et al, 2006;Gur et al, 2011;Lee et al, 2011) and previous metaanalysis gave an inconsistent result (Tsilidis et al, 2008;Heikkila et al, 2009). All above-mentioned information seemed to support the results of this meta-analysis that the association between CRP levels and cancer risk is site-specific, and significant with lung cancer, weak with breast, colorectal and prostate cancer.…”
Section: Discussionsupporting
confidence: 61%
“…In accordance with the result of previous meta-analysis (Heikkila et al, 2009), less epidemiologic studies suggested a significant association between the elevated CRP levels and an increased risk of prostate and breast cancer (Platz et al, 2004;Trichopoulos et al, 2006), although a role for chronic inflammation in prostate (Haverkamp et al, 2008) and breast cancer (Ben-Baruch, 2003) has been identified. More controversy seemed to be from colorectal cancer (Otani et al, 2006;Gur et al, 2011;Lee et al, 2011) and previous metaanalysis gave an inconsistent result (Tsilidis et al, 2008;Heikkila et al, 2009). All above-mentioned information seemed to support the results of this meta-analysis that the association between CRP levels and cancer risk is site-specific, and significant with lung cancer, weak with breast, colorectal and prostate cancer.…”
Section: Discussionsupporting
confidence: 61%
“…A number of epidemiological studies investigated the association between biomarkers of chronic inflammation, particularly CRP and colorectal cancer risk. High blood concentrations of CRP have been associated with moderately higher CRC risk in several prospective studies [87][88][89] including in the EPIC study [90]. However, findings from observational studies relating circulating CRP to cancer risk may not necessarily reflect causal associations.…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…CRP, which is an acute-phase protein that displays a rapid and distinct rise in its plasma concentration in response to acute inflammation, infection and tissue damage, has been examined in studies as a marker of chronic inflammatory states (16)(17)(18). Most critically, CRP has been reported to be elevated in epidemiologic studies, in some studies marking the presence of prevalent cancer (19), but also associated with an increased risk of future cancer in otherwise healthy individuals (16,(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%